2008
DOI: 10.1007/s10439-008-9453-8
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Flux in Neutrophils Synchronizes β2 Integrin Adhesive and Signaling Events that Guide Inflammatory Recruitment

Abstract: Abstract-Intracellular calcium flux is an early step in the signaling cascade that bridges ligation of selectin and chemokine receptors to activation of adhesive and motile functions during recruitment on inflamed endothelium. Calcium flux was imaged in real time and provided a means of correlating signaling events in neutrophils rolling on E-selectin and stimulated by chemokine in a microfluidic chamber. Integrin dependent neutrophil arrest was triggered by E-selectin tethering and ligation of IL-8 seconds be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 51 publications
9
117
0
1
Order By: Relevance
“…Our results went beyond questioning the value of anti-staphylococcal antibodies in prevention of infections by S. aureus (as some studies have found that high titers of antibodies to S. aureus are not effective in preventing re-infection [16][17][18][19][20] ), but supported the hypothesis that the manner by which PVL plays a role in CA-MRSA pathogenesis is by antibody-mediated neutralization of the host's innate response activated by sub-lytic amounts of PVL produced early in the course of infection. Mechanistically, we confirmed that sub-lytic concentrations of PVL induced the opening of calcium ion channels in PMNs, 21,22 a hallmark of PMN activation, 23 and showed that antibodies directed to PVL inhibited this activation (Fig. 2B).…”
Section: Bacterial Cytotoxins As Immune Activators: Harmful or Benefisupporting
confidence: 69%
“…Our results went beyond questioning the value of anti-staphylococcal antibodies in prevention of infections by S. aureus (as some studies have found that high titers of antibodies to S. aureus are not effective in preventing re-infection [16][17][18][19][20] ), but supported the hypothesis that the manner by which PVL plays a role in CA-MRSA pathogenesis is by antibody-mediated neutralization of the host's innate response activated by sub-lytic amounts of PVL produced early in the course of infection. Mechanistically, we confirmed that sub-lytic concentrations of PVL induced the opening of calcium ion channels in PMNs, 21,22 a hallmark of PMN activation, 23 and showed that antibodies directed to PVL inhibited this activation (Fig. 2B).…”
Section: Bacterial Cytotoxins As Immune Activators: Harmful or Benefisupporting
confidence: 69%
“…Previous studies have found that the induction of proinflammatory cytokine release by PMNs exposed to sublytic levels of PVL results from the opening of calcium ion (Ca 2+ ) channels, which is a necessary step in PMN activation (16). We next explored whether antibodies to PVL affected PVL-mediated Ca 2+ influx into PMNs by measuring the emission of fluorescence by cells preloaded with a calcium indicator.…”
Section: Resultsmentioning
confidence: 99%
“…To assay adhesive strength of LPS-treated WT and CD14 2/2 neutrophils in vitro, vascular mimetic microfluidic chambers (a generous gift from Scott Simon, Department of Biomedical Engineering, University of California, Davis, Davis, CA) were used. As previously described (19), the chamber consists of a single channel 600 mm in width and 70 mm in height and uses a network of vacuum channels to reversibly bind to a layer of adhesion molecules. Coverslips were coated with 10% heat-inactivated mouse serum at room temperature for 3 to 4 h to allow for adhesion.…”
Section: Murine Neutrophil Adhesive Strength Assaymentioning
confidence: 99%